Viewing Short Gamma-Ray Bursts From a Different Angle - Burgess, J. Michael; Greiner, Jochen; Bégué, Damien; Giannios, Dimitrios; Berlato, Francesco; Lipunov, Vladimir M. (Frontiers in Astronomy and Space Sciences, 2020)
The detection of a faint, short gamma-ray burst (GRB) in coincidence with the gravitational wave (GW) detection by aLIGO/Virgo is at odds with the expected known luminosity and redshift distribution of short GRBs (sGRB). Examining the observer-frame parameter space of all Fermi-GBM sGRBs shows that the sGRB associated with GW 170817A is extreme in its combination of flux, spectral softness and temporal structure. We identify a group of similar GRBs, one of which has been associated to a bright galaxy at​ 75 Mpc. We speculate that a good fraction of the previously detected faint sGRBs is not at large redshifts, but local, at redshift smaller than 0.1, seen off- axis. We incorporate off-axis emission in the estimate of the rates of sGRBs, and predict that the majority of future GW-detections of NS-NS mergers will be accompanied by faint γ-ray emission, contrary to previous thinking. The much more frequent off-axis emission of sGRBs also implies a higher deadly rate of -rays for extraterrestrial life in the Universe.